Odpowiedzi

2010-01-10T17:55:36+01:00
X+y=15 *(-6) (mnożymy przez -6)
6x+12y=120

-6x-6y=-90
6x+12y=120

6y=30
y=5

x+5=15
x=10

y=5
x=10

spr.
x+y=15
6x+12y=120

10+5=15
6*10+12*5=120 60+60=120
2010-01-10T17:56:02+01:00
X+y=15
6x+12y=120|:6

y=15-x
x+2y=20

y=15-x
x+2(15-x)=20

y=15-x
x+30-2x=20

y=15-x
x-2x=20-30

y=15-x
-x=-10|:(-1)

y=15-x
x=10

y=15-10
y=5

2010-01-10T17:56:07+01:00
X+y=15
6x+12y=120

x = 15 - y
6* (15 - y) + 12y = 120

x = 15 - y
90 -6y +12y = 120

x = 15 -y
6y = 30 /:6

x = 15 -y
y = 5

x = 10
y = 5
1 5 1